Development and Implementation of the AIDA International Registry for Patients With Undifferentiated Systemic AutoInflammatory Diseases - Della Casa, Francesca; Vitale, Antonio; Lopalco, Giuseppe; Ruscitti, Piero; Ciccia, Francesco; Emmi, Giacomo; Cattalini, Marco; Wiesik-Szewczyk, Ewa; Maggio, Maria Cristina; Ogunjimi, Benson; Sfikakis, Petros P.; Tufan, Abdurrahman; et al. (Frontiers in Medicine, 2022)
Objective: This paper points out the design, development and deployment of the AutoInflammatory Disease Alliance (AIDA) International Registry dedicated to pediatric and adult patients affected by Undifferentiated Systemic AutoInflammatory Diseases (USAIDs). Methods: This is an electronic registry employed for real-world data collection about demographics, clinical, laboratory, instrumental and socioeconomic data of USAIDs patients. Data recruitment, based on the Research Electronic Data Capture (REDCap) tool, is designed to obtain standardised information for real-life research. The instrument is endowed with flexibility, and it could change over time according to the scientific acquisitions and potentially communicate with other similar tools; this platform ensures security, data quality and data governance. Results: The focus of the AIDA project is connecting physicians and researchers from all over the world to shed a new light on heterogeneous rare diseases. Since its birth, 110 centres from 23 countries and 4 continents have joined the AIDA project. Fifty-four centres have already obtained the approval from their local Ethics Committees. Currently, the platform counts 290 users (111 Principal Investigators, 179 Site Investigators, 2 Lead Investigators, and 2 data managers). The Registry is collecting baseline and follow-up data using 3769 fields organised into 23 instruments, which include demographics, history, symptoms, trigger/risk factors, therapies, and healthcare information access for USAIDs patients. Conclusions: The development of the AIDA International Registry for USAIDs patients will facilitate the online collection of real standardised data, connecting a worldwide group of researchers: the Registry constitutes an international multicentre observational groundwork aimed at increasing the patient cohort of USAIDs in order to improve our knowledge of this peculiar cluster of autoinflammatory diseases. NCT 05200715 available at https://clinicaltrials.gov/.